Preschool father-child attachment and its relation to self-reported child socioemotional adaptation in middle childhood. Issue 1 (2nd January 2020) - Bureau, Jean-François; Deneault, Audrey-Ann; Yurkowski, Kim
ABSTRACT: Although considerable research has sought to establish the influence of parent-child attachment on child socioemotional adaptation, it has primarily focused on mother-child dyads and external reports of adaptation. The current study investigates the longitudinal associations between both preschool mother-child and father-child attachment and self-reported socioemotional adaptation in middle childhood. Eighty-three children (47 girls) participated in separate lab visits with each parent at both Time 1 (3–5 years old) and Time 2 (7–11 years old). Results revealed that father-child attachment assessed with the MacArthur Preschool Attachment Coding System was uniquely related to child self-esteem, such that insecure children had significantly lower self-esteem scores than what was expected by chance. Children insecurely attached to their father also reported significantly higher externalizing problems than secure children, but this relationship was only significant if the child was also insecurely attached to their mother.